The Impact of Thinking Fast and Slow on the Evangelical Mind - Devers, Erin E. (Christian scholar's review, 2018)
At first blush, the idea of thinking fast sounds desirable. In our culture, doing things quickly is often more highly valued than taking time. This preference translates into a tendency to give precedence to activities that do not require deep thought. Although it feels strange to have to make this argument, this preference for shallow thinking has had, and will continue to have, negative consequences for our culture, the evangelical subculture, and the broader church.